2005
DOI: 10.1111/j.1477-9730.2005.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Epipolar Geometry in Linear Array Scanner Scenes

Abstract: Resampled imagery according to epipolar geometry, usually denoted as normalised imagery, is characterised by having conjugate points along the same row (or column). Such a characteristic makes normalised imagery an important prerequisite for many photogrammetric activities such as image matching, automatic aerial triangulation, automatic digital elevation model and orthophoto generation, and stereo viewing. The normalisation process requires having the input imagery in a digital format, which can be obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…It was based on the researches presented by Habib et al [7] and Kim [2]. These previous works showed that epipolar curves of linear pushbroom images are not lines but hyperbola-like non-linear curves and that an epipolar curve for the entire image can only be approximated by piecewise linear segments, with epipolar curve pairs Fig.…”
Section: Image Space-based Methodsmentioning
confidence: 99%
“…It was based on the researches presented by Habib et al [7] and Kim [2]. These previous works showed that epipolar curves of linear pushbroom images are not lines but hyperbola-like non-linear curves and that an epipolar curve for the entire image can only be approximated by piecewise linear segments, with epipolar curve pairs Fig.…”
Section: Image Space-based Methodsmentioning
confidence: 99%
“…In contrast to frame cameras, the epipolar geometry of the satellite pushbroom sensors shows different behaviour. The epipolar curves of the pushbroom cameras are not straight and the conjugate pair does not exist (Morgan et al, 2004;Oh et al, 2010;Habib et al, 2005). Therefore, the commonly used techniques for stereo rectification of frame cameras can't be directly applied for rectification of images from pushbroom sensors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several techniques have been proposed for pushbroom rectification with the affine camera model approximation being the most popular solution for pushbroom rectification. The affine assumption is suitable due to the following reasons: the height variations in the object space are small compared to the satellite altitude, the angular field of view is small and the satellite is assumed to travel in a straight line with a constant velocity (Morgan et al, 2004;Habib et al, 2005) during the short image acquisition time. An affine transformation is estimated using corresponding points between the two images and the resulting transformation causes the corresponding points to lie along the same image rows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using various pushbroom camera models (Orun andNatarajan, 1994, Hartley andGupta, 1997), it can be shown that pushbroom image pairs have non-straight epipolar curves and that these curves are not conjugate, making rectification impossible (Kim, 2000, Habib et al, 2005.…”
Section: The Stereo Image Rectification Problemmentioning
confidence: 99%